The Legal Framework for Brazilian Biodiversity and the Free Prior Informed Consent (FPIC) for Traditional Peoples - Marcos Vinicio Chein Feres (Journal of Legal Studies & Research, 2024)
The legislation proposes the protection of traditional knowledge and the regulation of the use of biodiversity in Brazil. The article provides a detailed account of the legislative process, including an analysis of the mechanisms, actors, and pathways involved and an examination of the role of legal persons in interpreting the interactions between official agents and traditional peoples’ representatives. Specifically, the article examines how the legislation was conceived and approved, with specific attention to the perspectives expressed by traditional peoples during the process. The research methodology involves the collection of the proposed bill, its transcripts, and the written and oral statements of associations or individuals representing the interests of traditional peoples. The objective is to establish a descriptive category that reflects the procedural aspects (mechanisms, pathways) of this legislation and the perceptions of traditional peoples (actors) regarding this particular legal framework, which is known as the Brazilian legal benchmark of biodiversity.